STRATEGI KOMUNIKASI INFLUENCER HALAL DALAM MENYAMPAIKAN PRODUK SECARA SYARIAH SEBAGAI UPAYA EDUKASI SYARIAH - Merinda Hana Aulia; Nabilah Fitriyani (Gunung Djati Conference Series, 2025)
The rapid growth of the halal industry in Indonesia reflects the increasing awareness of the Muslim community towards the importance of consuming products that comply with Islamic law. Social media is now the main medium for disseminating halal information, where the role of halal influencers is vital as a link between producers and consumers. This study aims to identify the communication strategies used by halal influencers in conveying sharia-compliant products, as well as their role in educating the public through a digital content approach. The research method uses a qualitative-descriptive approach through literature study, social media content analysis, and in-depth interviews. Case studies of influencers such as @aishamaharani, @dianwidayanti, and @halalcorner account show that an honest, educational, and aligned with Islamic values communication approach is able to build trust and influence halal consumption patterns, especially among the younger generation. This research confirms that sharia education through digital media is a strategic tool in strengthening Indonesia's halal ecosystem.